Differential biomarker profiles between unprovoked venous thromboembolism and cancer. (17th August 2020) - Sánchez-López, V.; Gao, L.; Ferrer-Galván, M.; Arellano-Orden, E.; Elías-Hernández, T.; Jara-Palomares, L.; Asensio-Cruz, M. I.; Castro-Pérez, M. J.; Rodríguez-Martorell, F. J.; Lobo-Beristain, J. L.; Ballaz-Quincoces, A.; López-Campos, J. L.; et al.
Abstract: Background: The relationship between cancer and venous thromboembolic disease (VTD) are complex because the activated coagulation factors are not only involved in thrombosis but also in malignant processes, such as angiogenesis and metastasis. Objective: To compare phenotypes of extracellular vesicles (EVs), and levels of D-dimer, soluble P-selectin (sP-selectin) and antigenic tissue factor (TF) between unprovoked VTD patients, who did not develop cancer during one-year follow-up, and those with advanced stage of cancer but not associated with VTD. Methods: A prospective study in which we included 138 unprovoked VTD patients and 67 advanced cancer patients, who did not develop thrombosis. Levels of EVs of different cellular origin (platelet, endothelium and leukocyte), EVs positive for tissue factor (TF) and P-selectin glycoprotein ligand 1 were quantified by flow cytometry. D-dimer, soluble P-selectin (sP-selectin) and antigenic TF were determined by ELISA. Results: TF-positive EVs, D-dimer, and sP-selectin were markedly elevated in unprovoked VTD patients compared to cancer patients without association with thrombosis. Conclusions: Levels of TF-positive EVs, D-dimer and sP-selectin are able to discriminate between unprovoked VTD patients not related to cancer and cancer patients not associated with VTD. These results could lead to the application of EVs as biomarkers of both diseases. Key messages : Circulating EVs, specifically TF-positive EVs, in combination with plasmatic markers of hypercoagulable states, such as D-dimer, sP-selectin and antigen TF, are able to discriminate between cancer patients without thrombosis and patients with unprovoked VTD. Research fields could be opened. Future studies will assess if these biomarkers together serve as predicting thrombotic events in cancer populations